PENGARUH SISTEM PENGENDALIAN INTERNAL, BUDAYA ORGANISASI DAN TUNJANGAN KINERJA TERHADAP PELAKSANAAN ANGGARAN KEMENTERIAN KOPERASI DAN USAHA KECIL DAN MENENGAH - Binsar H Simanjuntak; Hengki Andrianto (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2018)
Purpose of this research are to known that there is an influence between Internal Control System, Organization Culture and Performance Incentive to Fraud Triangle. Population in this research are Government Employee at Cooperative, Small and Medium Enterprises Ministry. We used convenience sampling, and we succeed have about 208 respondents in this research. Test results with multiple regression found that the Internal Control System and Performance Incentive did not influence to the fraud triangle and there is a negative influence Organizational Culture to the fraud triangle on budget implementation at Ministry of Cooperatives and SMEs